Surface Nanobubbles Are Stabilized by Hydrophobic Attraction - Tan, Beng Hau (2018)
The remarkably long lifetime of surface nanobubbles has perplexed researchers for two decades. The current understanding is that both contact line pinning and supersaturation of the ambient liquid are strictly required for the stability of nanobubbles, yet experiments show nanobubbles surviving in open systems and undersaturated environments. We find that this discrepancy can be addressed if the effects of an attractive hydrophobic potential at the solid substrate on the spatial distribution of the gas concentration is taken into account. We also show that, in our model, only substrate pinning is strictly required for stabilization; while hydrophobicity and supersaturation both aid stability, neither is mandatory—the absence of one can be compensated by an excess of the other.